How to Manage the Foreclosure Process - Michael S. Gutter; Travis P. Mountain; Lisa Leslie; Laura Royer (EDIS)
FCS-3269, a 4-page fact sheet by Michael S. Gutter, Travis P. Mountain, Lisa Leslie, and Laura Royer, explains the foreclosure process and what to do when facing foreclosure. Includes references. Published by the UF Department of Family Youth and Community Sciences, June 2008.